Characteristics of Staphylococcus aureus isolated from rabbits - Simonová, M; Fotta, M; Lauková, A (Folia microbiologica, 2007)
The occurrence of Staphylococcus aureus in rabbit feces, cecum and meat and its enterotoxin production, susceptibility to antibiotics and its sensitivity or resistance to bacteriocins produced by enterococci with probiotic properties were determined. Isolates were resistant to ampicillin, penicillin, phosphomycin and methicillin; a high percentage of susceptibility was also recorded to vancomycin, chloramphenicol, tetracycline and tobramycin. S. aureus isolates did not produce enterotoxins and were sensitive to partially purified enterocins (PPB) EK13, AL41 and EF2019 in the range of 100 to 12800 AU/mL; all S. aureus isolates, except the strain SA 2A/3, exhibited the highest sensitivity to PPB EK13. On the other hand, all strains were resistant to PPB CCM4231.
Keywords: Drug Resistance, Multiple, Bacterial; Feces; Male; Slovakia; Slovenská republika; maso; Staphylococcus aureus; rezistence na methicilin; mnohočetná bakteriální léková rezistence; Microbial Sensitivity Tests; Methicillin Resistance; cékum; mužské pohlaví; Cecum; králíci; Bacteriocins; bakteriociny; přemostěné cyklické sloučeniny; Animals; hospodářská zvířata; ženské pohlaví; Animals, Domestic; Bridged-Ring Compounds; zvířata; mikrobiální testy citlivosti; Rabbits; Meat; Female; feces